Comparative Study of Intensity and Pitch of Sounds of Some Domestic Animals and Birds - Adhikari, S.K.; Adhikari, N.P.; Aryal, R. K. (BMC Journal of Scientific Research, 2024)
Sound serves as a versatile form of communication. Animals and birds utilize sound for various purposes, including communication, marking territory, hunting prey, alerting others to danger, and attracting mates. Research into the sound analysis of some domestic animals and birds has become a prominent field of study. This study aims to determine the intensity and pitch of sounds produced by domestic animals and birds. Primary data was collected using a SONY IC RECORDER, and the sounds were analyzed for intensity and pitch with PRAAT software. Experimentally, it found that the mean intensity values for animal sounds ranged from 53.98 dB to 83.14 dB, with an average of 72.80 dB, while the mean pitch values ranged from 80.38 Hz to 841.74 Hz, averaging at 431.70 Hz. In contrast, the mean intensity for bird sounds spanned from 63.08 dB to 81.01 dB, averaging 73.08 dB, and the mean pitch values ranged from 299.17 Hz to 2145.00 Hz, with an average of 1214.93 Hz. The comparison of average mean values for intensity and pitch yielded ratios of 1.01 and 2.81, respectively. This indicates that, on average, the intensity of bird sounds is slightly higher than that of animal sounds, while their pitch values are significantly higher. Such findings contribute to identifying distinct pitch ranges and intensity levels among various birds and animals.